VD_FINDINFO Jug / 2016 / 232 vom 18. November 2015 - VD Tribunal cantonal (2015)
BRIGANDAGE, CHOSE VOLÉE, INCENDIE INTENTIONNEL, IN DUBIO PRO REO, CONSTATATION DES FAITS | 139 CP, 140 CP, 221 CP, 10 CPP (CH)